Occupational Safety and the City: Licensing Regulation and Deregulation in the Taxi Sector - Reid-Musson, Emily; MacEachen, Ellen; Bartel, Emma; Saunders, Ron; Meyer, Samantha; Bigelow, Philip (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2020)
Many large cities in North America have jurisdiction over licensing rules that shape the employment and health conditions of ride-hail and taxi drivers. Yet there is a lack of research on the role of licensing agencies relating to the occupational health and safety (OHS) of taxi drivers. Most taxi and ride-hail drivers in Canada are self-employed workers and are, by default, exempt from OHS and worker compensation laws. Additionally, municipal licensing regimes in Canada and the US have undergone various changes as a result of pressures from new platform-based ride-hail services, like Uber and Lyft.The analysis is part of a larger study on the health and safety conditions faced by ride-hail drivers. The research approach adopted a multi-level sampling and analysis strategy with the aim of connecting taxi drivers’ everyday work experiences to company and sector practices, and with various regulatory arenas, including municipal licensing, taxation and car insurance. In this paper, the analysis draws from in-depth interviews at these different levels: with taxi and ride-hail drivers, with taxi and ride-hail managers, and with key informants in government, law, insurance, tax and elsewhere.The paper identifies features and impacts of municipal deregulation in the era of on-demand taxi services, focusing on a large Canadian city in a province where municipal authorities regulate the vehicle-for-hire sector. The research identified regulatory changes that included removing centralized taxi vehicle inspections, cancelling mandatory driver training, and instigating rapid changes to competition in the taxi workforce by issuing unlimited numbers of ride-hail licenses. Our analysis indicates that regulatory changes adopted by the city administration have compounded work vulnerabilities and hazards for taxi drivers, while extending hazardous conditions to ride-hail drivers. These hazards suggest the need for interventions at a range of levels, actors and agencies, rather than solely by city licensing officials.